UJI SENSORIS PADA PENGEMBANGAN PRODUK MINUMAN OLAHRAGA BERBASIS JAMUR TIRAM DAN UBI JALAR - Yuni Afriani; Sri Kadaryati (Universitas Respati Yogyakarta, 2021)
Sensory Evaluation on Sport Drink Development Product Based on Oyster Mushroom and Sweet PotatoBackground: sports drinks are consumed to improve of athlete's performance. Sport drink based on oyster mushroom has the potential to be develop. Purple sweet potato and Cilembu are a source of carbohydrates, sodium, potassium, and antioxidants. The development of sports drink based on oyster mushrooms and sweet potatoes is carried out to produce sports drink that are more organoleptically acceptable and in accordance with the requirements of sports drinks. Objective: this study aims to determine the sensory evaluation of a sports drink product formula based on oyster mushrooms and sweet potatoes. Methods: this research was a laboratory observational study through the stages of flour process, analysis of nutrients (proximate, sodium, and potassium), formulation products and organoleptic tests. The product formulation consists of oyster mushroom flour, purple/ cilembu sweet potato flour, water, NaCl, and sugar/ maltodextrin. Sensory tests were carried out on 31 semi-trained panelists at the Dietetic/ Culinary Laboratory of Universitas Respati Yogyakarta by assessing the color, aroma, taste, viscosity, and overall. Data were analyzed using Mann Whitney test. Results: the formula made from cilembu sweet potato flour was preferable to purple sweet potato flour. Sugar produce the preference better than maltodekstrin. Products with oyster mushroom flour, cilembu sweet potato flour, water, NaCl, and granulated sugar are more sensory accepted in the development of sports drink products and in accordance with the requirements of sports drinks. Conclusion: products made from oyster mushroom flour, cilembu sweet potato, water, NaCl, and sugar are more sensory acceptance.